Identification of nutrient composition of some isolated microalgae from mangroves of Xuan Thuy national park - Tuan, Le Xuan; Hang, Tran Thi Minh (Academia Journal of Biology, 2018)
Microalgae species, such as Amphiprora alata, Chaetoceros muelleri, Nannochloropsis oculata, Navicula tuscula and Chlorella vulgaris from mangrove area of Xuan Thuy National Park are usually used as food sources for fishes, shrimps and bivalves and very environment friendly. The samples of these microalgae were enriched, isolated and purified in F/2 medium with salinity of 20%. The purifed colonies were cultured in media with different salinity in 14 days to find out the most optimal medium for the best growth as well as the stage yielding maximum living mass. These microalgae were then cultured in their optimal media at salinity of 25% until they reached their maximum living mass stage. They were cultivated and analyzed of their fatty acid, protein carbonhydrate components and percentages. The research has identified 24 fatty acids in 5 phytoplankton species. Unsaturated fatty acids components of Chaetoceros muelleri, Nannochloropsis oculata are the highest (76,35% and 71,17%), and fatty acid components of are medium Chlorella vulgaris and Amphiprora alata (59,24% and 52,21%), meanwhile, Navicula tuscula has 29.56% of unsaturated fatty acids.  Amphiprora alata and Chlorella vulgaris have protein content of 8.1g per 100g dry weight and 4.44g per 100g dry weight accordingly. Carbohydrate content of Nannochloropsis oculata and Navicula tuscula are 11.8g per 100g dry weight and 5.47g per 100g dry weight, respectively.